UTILIZING PADLET APPLICATION ON WRITING ACTIVITIES: EFL LEARNERS VIEWS - Mega, Iful Rahmawati; Aprilliandari, Dwi Indra (IJIET (International Journal of Indonesian Education and Teaching), 2025)
The objectives of this research determined the students perception of using the Padlet Application through writing activities. Padlet is the digital equivalent of sticking post it notes to the wall for organizing students' writing; the entire class can use it to organize ideas, brainstorm, comment, and create a stream of text and images. Students of EFL Writing Class were the subject of this research. The study used descriptive qualitative research with the questionnaire survey to collect the data. Based on the researchers survey, all the data was analyzed descriptively to describe learners views. The researcher offers some questions in the form of a questionnaire that focuses on using Padlet through writing class. The research results are based on students views that Padlet is easier to use, students enjoy the writing class, students are more interested in writing activities, and students feel motivated to complete the writing. Meanwhile, the challenge of using Padlet is the internet connection. So, most of the students believed that using Padlet to help their writing process was useful. Padlet is an effective tool for students to do writing activities and stay motivated.